Formulation and characterization of screen printable dopant ink for fabrication of polysilicon TFTs. (26th May 2021) - Ito, Mao; Kamath, Arvind
Abstract: To move the promise of printed electronics from the laboratory to volume production required adopting a new approach eliminating ink-jet printing and adopting instead a hybrid mature print and conventional process. Novel screen printable N+ and P+ dopant inks were developed to fabricate polysilicon thin film transistors (TFTs). Semiconductor-grade dopant inks were formulated from a combination of thermoset plastic with boron and phosphor compounds. Inks were screen printed on polysilicon active islands on a 300 mm square stainless-steel foil substrate. The drain and source of the top gate TFTs were then formed via a thermal anneal activation. The residue after annealing was removed with an inoffensive process to avoid damage to the thin silicon layer and gate oxide. Doping was uniform across 300 mm sheet substrate. The sheet resistance was modulated to 200 Ω sq −1 for the N+ and 1000 Ω sq −1 for the P+ active layer. Field mobility of polysilicon TFTs fabricated using this screen-printed dopant process were 80 cm 2 V s −1 for PMOS and 200 cm 2 V s −1 for NMOS using low-cost, mature equipment, and an easily manageable process that is both scalable and compatible with roll-to-roll manufacturing.